-2+3(-6y-7)=-5(-5y-1)+2

Simple and best practice solution for -2+3(-6y-7)=-5(-5y-1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+3(-6y-7)=-5(-5y-1)+2 equation:


Simplifying
-2 + 3(-6y + -7) = -5(-5y + -1) + 2

Reorder the terms:
-2 + 3(-7 + -6y) = -5(-5y + -1) + 2
-2 + (-7 * 3 + -6y * 3) = -5(-5y + -1) + 2
-2 + (-21 + -18y) = -5(-5y + -1) + 2

Combine like terms: -2 + -21 = -23
-23 + -18y = -5(-5y + -1) + 2

Reorder the terms:
-23 + -18y = -5(-1 + -5y) + 2
-23 + -18y = (-1 * -5 + -5y * -5) + 2
-23 + -18y = (5 + 25y) + 2

Reorder the terms:
-23 + -18y = 5 + 2 + 25y

Combine like terms: 5 + 2 = 7
-23 + -18y = 7 + 25y

Solving
-23 + -18y = 7 + 25y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-25y' to each side of the equation.
-23 + -18y + -25y = 7 + 25y + -25y

Combine like terms: -18y + -25y = -43y
-23 + -43y = 7 + 25y + -25y

Combine like terms: 25y + -25y = 0
-23 + -43y = 7 + 0
-23 + -43y = 7

Add '23' to each side of the equation.
-23 + 23 + -43y = 7 + 23

Combine like terms: -23 + 23 = 0
0 + -43y = 7 + 23
-43y = 7 + 23

Combine like terms: 7 + 23 = 30
-43y = 30

Divide each side by '-43'.
y = -0.6976744186

Simplifying
y = -0.6976744186

See similar equations:

| 6=3+y | | x^2+3x-7=32 | | x^2+x+10=35 | | x^2+3x+4=16 | | x+10=24-x | | x^2+x-7=3 | | x^2+x-7=14 | | 0=44x^2-88x+74 | | 0=44x^2-88t+74 | | x^3+3=14 | | 24=4m | | -7(2x+3)+11x= | | x^2+2x+1=40 | | G=9/2(p-67) | | x=1-13/5 | | 5x+13y+5=0 | | -11-(-15)= | | -3(4r-80)=-36 | | 180=4/(x-4) | | y=2(x-7) | | w-(4/2/5)=(9/3/5) | | 11-x=19 | | 13+w/7 | | (m-3)=5 | | 7y+14=-15y+10+6y | | 16x+42-13x=20+4 | | 10a+a-7a= | | X/3+3=x/2+2 | | 2=(n+1) | | 2(p+3)=8 | | 6x+37=14x-32 | | 4x-5+2x=7x-1 |

Equations solver categories